ON DIFFERENTIAL DIAGNOSIS BETWEEN AUTISTIC DISORDER AND ASPERGER'S SYNDROME - Stefan Todorov; Mariana Arnaoudova (Peytchinski Publishing, 2012)
The differential diagnosis between Autistic disorder (AD) and Asperger's syndrome (AS) in most cases is quite difficult since most of the symptoms are clinically undistinguished. Several factors complicate the diagnosis of AS- an autism spectrum disorder (ASD). It is considered by some authors to be simply a milder version of autistic disorder. Problems in diagnosis include disagreement among diagnostic criteria, controversy over the distinction between AS and other ASD forms or even whether AS exists as a separate syndrome, and over- and under-diagnosis. Our paper is based on the diagnostic and differential diagnostic criteria of DSM-IV, ICD-10 and our clinical experience.In the process of diagnosis and differential diagnosis we, naturally, illustrate and discuss the similarities and differences between the two disorders.